Transgender Dan Hak Asasi Manusia Dalam Tinjauan Maqashid Syariah: Hifdzul ‘Aql - Aisyah, Nagita Histimuna; Nurfida, Aminah; Nafisa, Elly Zakiyatin; Lutfiyah, Lutfiyah; Kahfi, Nazih Sadatul (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2024)
This research aims to examine the transgender issue more comprehensively which focuses on the purpose of human benefit and welfare in terms of maqashid sharia and also human rights perspective through the understanding of hifdzul 'aql. This research is a qualitative research that uses this analysis method and uses literature study techniques in data collection. The results of this study show that transgender issues involve a complexity of social and cultural norms that differ between Muslim and non-Muslim societies. In non-Muslim countries, legal protections and health access for transgender people are rapidly growing, whereas in Muslim-majority countries, conservative views often reject gender change. Human rights play an important role in protecting transgender rights, while Maqashid Sharia principles can provide a just framework in the context of Muslim societies, emphasizing the protection of soul, mind, and honor.